Automated surveillance in distributed, visual networks: an empirical comparison of recent algorithms - Ahmed, Tarem; Ahmed, Supriyo Sabbir; Pathan, Al-Sakib Khan (© 2014 Science and Engineering Research Support Society, 2016)
This article was published in the International Journal of Control and Automation [© 2014 Science and Engineering Research Support Society] and the definite version is available at: http://doi.org/10.14257/ijca.2014.7.3.37 The Article's website is at: http://www.sersc.org/journals/IJCA/vol7_no3.php